Virgil, the blind guide marking the way through the Divine Comedy - Howard, Lloyd (McGill-Queen's University Press, 2010)
Using hidden linguistic configurations, explores the issue of Virgil's authority in the Divine comedy as compared to other poets, guides, and demons.